Preventing facial pressure injury for healthcare providers adhering to COVID-19 personal protective equipment requirements - Hiske Smart, & Francis Byron Opinion, & Issam Darwich, Manal Aly Elnawasany and Chaitanya Kodange (WCET Journal - French Edition, 2020)
Objective  To determine if a repurposed silicone-based dressing used underneath an N95 mask is a safe and beneficial option for facial skin injury prevention without compromising the mask’s seal.  Methods  Since February 21, 2020, staff in high-risk areas such as the ED and ICU of King Hamad University Hospital have worn N95 masks when doing aerosol-generating procedures to protect against the novel coronavirus 2019. At that time, without education enablers or resources that could be directly translated into practice, the hospital’s Pressure Injury Prevention Committee explored and created a stepwise process to protect the skin under these masks. This procedure was developed over time and tested to make sure that it did not interfere with the effectiveness of the N95 mask seal. Results  Skin protection was achieved by repurposing a readily available silicone border dressing cut into strips. This was tested on 10 volunteer staff members of various skin types and both sexes who became part of this evidence generation project. Oxygen saturation values taken before and after the 4-hour wear test confirmed that well-fitted facial protection did not compromise the mask seal, but rather improved it. An added advantage was increased comfort with less friction as self-reported by the staff. An educational enabler to prevent medical device-related pressure injuries from N95 mask wear was an important additional resource for the staff. Conclusions  This creative and novel stepwise process of developing a safe skin protection method by which staff could apply a repurposed silicone border dressing beneath an N95 mask was largely effective and aided by the creation of the enabler.